A DEM numerical modelling approach to simulating size segregation of media in a stirred mill and effects on grind characteristics - Sievers, Wilco (Department of Chemical Engineering, 2026)
Comminution is an important operation in the minerals processing industry. In both traditional and stirred mills, single-sized grinding beads are used, along with multiple passes through the mills, to achieve a sufficient size-reduction ratio. It is plausible to expand the size reduction capabilities of a mill using multiple-sized grinding beads in the mill. For this study, the discrete element method (DEM) was used to simulate dry size-segregated systems in a vertical stirred mill. These size-segregated systems were evaluated at different impeller speeds and weight distributions. The dry systems were susceptible to the Brazilian nut effect. Furthermore, it was found that excessive impeller speeds did not subsequently increase the overall collision modulus. The overall modal collision intensity for particle collisions was maximised between 350 rpm and 500 rpm where sufficient mixing and impeller speed were facilitated. At excessive speeds past 700 rpm the collision modulus plateaued. Excessive addition of smaller particles reduced the total energy applied to particle-particle collisions which also reduced the overall systems collision modulus. The results presented in this study could be considered as an introduction to dry size-segregated media in a vertical stirred mill.